2015
DOI: 10.1002/mrd.22509
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression patterns of three aromatase genes and of four estrogen receptors genes in the testes of trout (Oncorhynchus mykiss)

Abstract: Estrogens are implicated in male gonad function, although their physiological roles remain uncertain. In the present study, we take advantage of the original model of spatio-temporal organization of trout spermatogenesis to revisit the synthesis and action sites of estrogens in fish testis. Within this system, somatic cell and germ cell development are synchronized due to a strict seasonal spermatogenetic cycle and the cystic organization of gonads. We evaluated the expression patterns and regulation of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…Such male-biased expression of estrogen receptors has been shown during late sexual differentiation for Nile tilapia (70dah) [ 49 ] and rainbow trout (60-110dpf) [ 110 ]. A recent study on rainbow trout also showed significantly elevated testicular expression of esr1a and esr2a during the final stage of spermiation, while esr1b and esr2b were expressed at early stages of testicular development [ 111 ]. In the same study, androgen implants up-regulated testicular esr1a , esr2a , and esr2b expression but down-regulated cyp19a1a expression, whereas estrogens reduced testicular cyp19a1a expression but increased the expression of cyp19a1b and esr1b .…”
Section: Resultsmentioning
confidence: 99%
“…Such male-biased expression of estrogen receptors has been shown during late sexual differentiation for Nile tilapia (70dah) [ 49 ] and rainbow trout (60-110dpf) [ 110 ]. A recent study on rainbow trout also showed significantly elevated testicular expression of esr1a and esr2a during the final stage of spermiation, while esr1b and esr2b were expressed at early stages of testicular development [ 111 ]. In the same study, androgen implants up-regulated testicular esr1a , esr2a , and esr2b expression but down-regulated cyp19a1a expression, whereas estrogens reduced testicular cyp19a1a expression but increased the expression of cyp19a1b and esr1b .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it is well known that P450 aromatase controls the synthesis of 17β-estradiol, one of the most relevant factors that locally controls spermatogenesis in non-mammalian (Cardone et al, 2002;Lance, 2009;Urbatzka et al, 2007;Burrone et al, 2012;Peñaranda et al, 2014;Delalande et al, 2015) and mammalian (O'Donnell et al, 2001;Carreau et al, 2007) vertebrates. In P. sicula, it is well known that high titres of 17β-estradiol are responsible for the spermatogenesis block (Angelini and Botte, 1992) and that 17β-estradiol production is under the control of VIP (Rosati et al, 2015) and PACAP , two neuropeptides involved in the control of lizard spermatogenesis (Agnese et al, 2010(Agnese et al, ,b,c, 2016Rosati et al, 2014aRosati et al, ,b, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…In non-mammalian vertebrate testes, investigations on P450 aromatase are limited to a few species: the trout Oncorhynchus mykiss (Delalande et al, 2015), the eel Anguilla anguilla (Peñaranda et al, 2014), the frogs Xenopus laevis (Urbatzka et al, 2007) and Pelophylax esculenta (Burrone et al, 2012), and the lizard Podarcis sicula (Cardone et al, 2002;Lance, 2009). In particular, in P. sicula, our experimental model, the partial coding sequence of P450 aromatase is known (gi 257359521), and it has been shown that the P450 aromatase inhibition by fadrozole modifies spermatogenesis, as well as the epididymis morphology (Cardone et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Gonadal estrogens are likely important in black sea bass testes, as both cyp19a1a and estrogen receptor beta (esr2b) were upregulated. Estrogen receptor alpha (esr1) was only slightly elevated, but may exhibit greater upregulation later during spermiation, as in rainbow trout (Oncorhynchus mykiss) (Bouma and Nagler, 2001;Delalande et al, 2015).…”
Section: Steroidogenesis and Estrogen Receptorsmentioning
confidence: 99%